PENCEGAHAN DAN PENANGANAN PERUNDUNGAN DI LINGKUNGAN SMKN 49 JAKARTA UTARA - Soeryowati, Poerwaningroem Lestari (Artinara, 2025)
Bullying incidents often occur in schools, homes, workplaces, communities, and even cyberspace. Bullying is any form of oppression or violence, which is carried out intentionally by one person or a stronger group. The purpose of this bullying is to hurt others and is carried out continuously. Bullying behavior can occur directly such as teasing, threatening, insulting, hitting, and robbing which is carried out by one or more students to the victim or other children. Bullying behavior is a crime committed by children, adolescents to adults so that this behavior cannot be considered normal, because it will have a negative impact on the victim. Bullying activities do not choose age and gender. The perpetrators choose someone from shy, quiet, special, beautiful, to having shortcomings to be used as a joke. Victims of bullying will feel depressed, insecure, afraid, worried and stressed when they come to school, then the victim will feel even more depressed and of course have a bad impact on their academic grades. Adolescence is a transitional age that needs to be watched out for in daily interactions at SMK 49 school, vulnerable to becoming victims or bullying behavior. Furthermore, in order for the learning process in schools to achieve its goals well and comfortably, this short lecture will provide new insights on how to prevent bullying behavior and how to deal with it. The results of the questionnaire consisting of 10 questions produced an average above 4.0, which means that female and male students of SMK 49 felt that this Abdimas program was effective, relevant and satisfying. Through this community service program, it is hoped that an inclusive school culture can be created, where every student feels valued, safe, and has an equal opportunity to develop. Strong character education and the formation of a positive social environment will be the foundation in preventing bullying and building a young generation with integrity and empathy. Concrete strategies and steps are needed in preventing and handling bullying in schools. The approach used includes education and training for all school residents, increasing awareness of the impacts of bullying, and implementing firm and fair policies. Keywords: Bullying; Teenagers; community service; prevention; handling